2012
DOI: 10.4103/0253-7176.106012
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing: An Updated Review

Abstract: Pain catastrophizing has been described for more than half a century which adversely affects the pain coping behavior and overall prognosis in susceptible individuals when challenged by painful conditions. It is a distinct phenomenon which is characterized by feelings of helplessness, active rumination and excessive magnification of cognitions and feelings toward the painful situation. Susceptible subjects may have certain demographic or psychological predisposition. Various models of pain catastrophizing have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
198
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(218 citation statements)
references
References 137 publications
(182 reference statements)
8
198
2
10
Order By: Relevance
“…Pain catastrophizing, depression, sleep disturbances, and physical health-related QOL Pain catastrophizing has been associated with both experimental and clinical pain experiences, 57 and it has been shown that reduction in levels of pain catastrophizing is associated with better treatment outcomes. 58 Similarly, a negative relation has been found between the presence of depression and decreased pain treatment responses, 59 whereas sleep disturbances are associated with hyperalgesia through descending modulatory systems.…”
Section: Worst Pain Intensitymentioning
confidence: 99%
“…Pain catastrophizing, depression, sleep disturbances, and physical health-related QOL Pain catastrophizing has been associated with both experimental and clinical pain experiences, 57 and it has been shown that reduction in levels of pain catastrophizing is associated with better treatment outcomes. 58 Similarly, a negative relation has been found between the presence of depression and decreased pain treatment responses, 59 whereas sleep disturbances are associated with hyperalgesia through descending modulatory systems.…”
Section: Worst Pain Intensitymentioning
confidence: 99%
“…Eccleston and Crombez (1999) stated that pain could emerge over other demands for attention; however, the interruptive function of pain depends on pain related characteristics (e.g., threat level of pain). Therefore, it may be that a catastrophizer has his or her attention disturbed to a state of cognitive and behavioral disruption whenever a painful stimulus occurs (Leung, 2012). Consequently, there is the possibility that mindfulness corresponds with pain catastrophizing because higher mindfulness prevents or diminishes this disruption.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The overall mean Catastrophizing score was low. This result is inconsistent with the literature on coping behaviors [33,34]. However, some authors have remarked on the concept of catastrophizing in children and adolescents [35,36,37,38].…”
Section: Psychological Factors In Pain Persistencementioning
confidence: 82%